Conceptual Criticism of Ombudsprudence in Indonesia and the Development of Good Ombudsnorm for Public Service Provision - Mursalim, Muliana; Pambudi. s, Rilo (Universitas Islam Negeri Walisongo Semarang, 2025)
In practice, Ombudsprudence is a collection of jurisprudence that highlights the success stories of recommendations issued by the Ombudsman. Consequently, the law's desired consistency and unity in handling maladministration cannot be effectively realized. The Ombudsprudence did not encourage the Ombudsman to consider previous recommendations in similar cases. This was a factor in the failure to achieve the ethics, fairness, and propriety recommended by the Ombudsman. This article aims to critique the adoption of Ombudsprudence in Indonesia. In addition, it seeks to purify the concept of Ombudsprudence to make it a tool for realising ombudsnorm and good administrative norms in public services. This article employs a non-doctrinal approach by collecting data through literature studies and interviews. The findings indicate that Ombudsprudence has been misinterpreted as merely a success story in case handling by the Ombudsman, which deviates from the basic idea and original concept in the Netherlands. In fact, the Ombudsman has established non-legal norms; however, misconceptions have led to its neglect as an ombudsman norm. Therefore, it is necessary to purify the concept by examining the indicators proposed by Langbroek and Rijpkema, so that Ombudsprudence aims to establish ombudsnorms in the form of norms of propriety produced by the Ombudsman, directed at creating good administrative norms as standards for exemplary public service in Indonesia. Ombudsprudensi dalam praktiknya merupakan kumpulan yurisprudensi yang menyoroti kisah sukses rekomendasi yang dikeluarkan oleh Ombudsman. Akibatnya, konsistensi dan kesatuan hukum yang diharapkan dalam menangani maladministrasi tidak dapat terwujud secara efektif. Ombudsprudensi tidak mendorong Ombudsman untuk mempertimbangkan rekomendasi sebelumnya dalam kasus serupa. Hal ini menjadi faktor kegagalan dalam mencapai etika, keadilan, dan kepatutan yang direkomendasikan oleh Ombudsman. Artikel ini bertujuan untuk mengkritisi penerapan Ombudsprudensi di Indonesia. Selain itu, artikel ini juga berupaya untuk memurnikan konsep Ombudsprudensi agar dapat menjadi alat untuk mewujudkan 'ombudsnorm' dan norma administrasi yang baik dalam pelayanan publik. Artikel ini menggunakan pendekatan non-doktrinal dengan mengumpulkan data melalui studi pustaka dan wawancara. Hasil penelitian menunjukkan bahwa Ombudsprudensi telah disalahartikan hanya sebagai kisah sukses dalam penanganan perkara oleh Ombudsman, yang menyimpang dari gagasan dasar dan konsep awal tentang Ombudsprudence di Belanda. Faktanya, Ombudsman telah menetapkan norma-norma non-hukum dan kesalahpahaman tersebut telah menyebabkan Ombudsprudensi diabaikan sebagai norma Ombudsman. Oleh karena itu, perlu dilakukan pemurnian konsep tersebut dengan mengkaji indikator-indikator yang diajukan oleh Langbroek dan Rijpkema, sehingga Ombudsprudensi bertujuan untuk menetapkan norma-norma Ombudsman yang berisi norma-norma kepatutan dan diarahkan untuk menciptakan norma-norma administrasi yang baik sebagai standar pelayanan publik yang patut dicontoh di Indonesia. Keywords: Ombudsman; Ombudsnorm; Ombudsprudence; Good Administration Norms